2022
DOI: 10.1002/brb3.2540
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Outcome of neurocritical disorders, a multicenter prospective cross‐sectional study

Abstract: Background: Patients with neurocritical disorders who require admission to intensive care units (ICUs) constitute about 10-15% of critical care cases. Objectives:To study the outcome of neurocritical disorders in intensive care units.Methodology: This is a prospective cross-sectional study that was conducted among neurocritical patients who were admitted in four intensive care units of four major hospitals in Khartoum state during the period from November 2020 to March 2021.Results: Seventy-two neurocritical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…En poblaciones neurocríticas no traumáticas y sin cáncer, los motivos de ingreso principales en UCI son similares a los neurooncológicos [26], [27].…”
Section: Motivo De Ingreso La Uciunclassified
“…En poblaciones neurocríticas no traumáticas y sin cáncer, los motivos de ingreso principales en UCI son similares a los neurooncológicos [26], [27].…”
Section: Motivo De Ingreso La Uciunclassified
“…Encephalitis is a neurological emergency caused by inflammation of the brain parenchyma and associated with a wide array of etiologies subdivided into two major groups: infectious encephalitis (IE) and autoimmune encephalitis (AE) [1]. Earlier epidemiological studies identified infectious pathogens as the main culprits behind encephalitis, whereas more recently, there has been a dramatic increase in the identification of AE associated with neuronal autoantibodies [2].…”
Section: Introductionmentioning
confidence: 99%
“…The disease is caused by an immunological impairment in neuromuscular transmission. The course of MG may be unstable, especially in the early stages of the disease and include the risk of crisis (Abuzinadah et al., 2020 ; Ali et al., 2022 ). It is well known that anxiety disorders and depression are considered common comorbidities in patients with MG and correlate with disease severity (Bogdan et al., 2020b ; Nadali et al., 2022 ; Suzuki et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%